Occupational exposure to PCDDs, PCDFs, and DL-PCBs in metallurgical plants of the Brescia (Lombardy Region, northern Italy) area. (January 2017) - Miniero, R.; Ingelido, A.M.; Abballe, A.; di Domenico, A.; Valentini, S.; Marra, V.; Barbieri, P.G.; Garattini, S.; Speziani, F.; De Felip, E.
Abstract: The concentration values of polychlorodibenzodioxins (PCDDs), polychlorodibenzofurans (PCDFs), and dioxin-like polychlorobiphenyls (DL-PCBs) in blood serum samples (pools) of metallurgical workers in the area of the city of Brescia (northern Italy) were statistically processed. As to workers' exposure characteristics, pools were divided into 34 professionally exposed (PE) and 11 non-professionally exposed (NPE). A further subdivision of PE pools was according to workplaces in which ferrous (N = 24) and non-ferrous (N = 10) materials were handled. To evaluate the aforesaid differences we applied the age-adjusted Generalized Linear Models. We identified significant (P ≤ 0.05) exposure models of the classification groups. The first subdivision was confirmed by the concentrations of 1, 2, 3, 4, 6, 7, 8-H7 CDF, DL-PCB 105, and DL-PCB 189; the second was confirmed by the concentrations of PCDF TEQ97, PCDD + PCDF + DL-PCB (TEQTOT ) TEQ97, 2, 3, 4, 7, 8-P5 CDF, 1, 2, 3, 6, 7, 8-H6 CDD, 1, 2, 3, 4, 6, 7, 8-H7 CDD, and PCB 189. Based on the literature, all mentioned congeners have been found in stack gas and fly ash samples of metallurgical plants: therefore, these indicators indicate the exposure to such work environments. Specifically, the concentrations measured in the workers' blood serum appear to depend on the type of material processed during work. Highlights: PCDDs + PCDFs and PCBs serum levels of metallurgical workers were investigated. Professionally (PE) and Not professionally (NPE) exposed subjects were considered. The PE group was further subdivided in ferrous and not ferrous work environments. Difference between not ferrous and ferrous work environments was observed. The congener-specific difference appears to correspond to the work environments.